Innovation Development of Russia and Participation in the Integration Process of the Asia-Pacific Region - Vorobeva, Natalia Alexandrovna; Beletskaya, Svetlana Alexandrovna; Kolesnikov, Mikhail Vladimirovich (International Journal of Economics and Financial Issues, 2016)
The article explores the innovation development of Russia and the integration process of the Asia-Pacific region. The analysis based on the evaluation of the level of innovation activities in the regions of Russia, which are the main basis of the innovation development of the whole country. Based on the calculations it was provided the dynamics of the main indicators of innovation activities of Russian regions. It was identified the existing imbalances between the innovation development of subsystem in the different regions. The analysis was completed by the comparison of the global indicators of knowledge-based economy in Russia and the leading countries of the Asia-Pacific region, which actively participate in the different innovation projects of the integration process of the Asia-Pacific region. It was identified that it is very important to develop the innovation infrastructure, the institutional environment of Russian regions with the aim of involving Russia in the integration processes of the leading countries of the Asia-Pacific region. Keywords: innovation, innovation development, integration process, Russia, Asia-Pacific region, JEL Classifications: Q4, O3